Predictors of Increased Daytime Sleepiness in Patients with Chronic Obstructive Pulmonary Disease: A Cross-Sectional Study. (16th October 2016) - Enz, Claudia; Brighenti-Zogg, Stefanie; Steveling-Klein, Esther Helen; Dürr, Selina; Maier, Sabrina; Miedinger, David; Leuppi, Jörg Daniel
Abstract : Background . Patients with Chronic Obstructive Pulmonary Disease (COPD) suffer from increased daytime sleepiness. The aim of this study was to identify potential predictors of subjective daytime sleepiness with special regard to sleep-related breathing disorder and nocturnal activity. Methods . COPD patients were recruited at the University Hospital Basel, Switzerland. COPD risk groups A–D were determined according to spirometry and COPD Assessment Test (CAT). Breathing disorder evaluation was performed with the ApneaLink device. Nocturnal energy expenditure was measured with the SenseWear Mini Armband. Subjective daytime sleepiness was recorded using the Epworth Sleepiness Scale (ESS). Results . Twenty-two patients (36%) were in COPD risk group A, 28 patients (45%) in risk group B, and 12 patients (19%) in risk groups C + D (n = 62 ). Eleven patients (18%) had a pathological ESS ≥ 10/24. ESS correlated positively with CAT (r = 0.386, p < 0.01 ) and inversely with age (r = - 0.347, p < 0.01 ). In multiple linear regression age (β = - 0.254, p < 0.05 ), AHI (β = 0.287, p < 0.05 ) and CAT score (β = 0.380, p < 0.01 ) were independent predictors of ESS, while nocturnal energy expenditure showed no significant association (p = 0.619 ). Conclusion . These findings provide evidence that daytime sleepiness in COPD patients may partly be attributable to nocturnal respiratory disturbances and it seems to mostly affect younger patients with more severe COPD symptoms.